Potensi Astragalus Sebagai Terapi Adjuvan Pada Pasien Glomerulonefritis - Alfina Indah Nabila; Nabila Rayhan Yasmin; Rani Himayani; Ramadhan Triyandi (Medula, 2023)
Glomerulonephritis is a medical term used to describe a condition that involves some kidney damages. Glomerulonephritis is an abnormality of the kidney that may lead to end-stage renal disease (ESRD). The current glomerulonephritis therapy is considered not fully effective due to the possibility of additional morbidity and complications that may occur. The use of Astragalus as adjuvant therapy can inhibit the progression of glomerulonephritis. The journals, that was reviewed, obtained from the Google Scholar, Sciencedirect, PubMed, and Springer with a publication year range of 2009-2023. The journals were selected to obtain valid and reliable journals, then do a literature review and article writing. Astragalus membranaceus has a bioactive content that can act as an immunomodulator, antiinflamation, and renoprotector. Astragalus is able to improve kidney function through IL-6 secretion and improve kidney interstitial fibrosis. Administration of Astragalus in combination with conventional therapy can reduce serum creatinine and proteinuria. Astragalus has potential as adjuvant therapy in glomerulonephritis patients.